Perencanaan Ulang Struktur Atas Jembatan Sambungrejo Sidoarjo dengan Menggunakan Prestressed Concrete I Girder - Azarine Carissa Yuniar; Nawir Rasidi; Wahiddin Wahiddin (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
This study aims to redesign the superstructure of the Sambungrejo Bridge in Sidoarjo, which has a span length of 16 meters. The Sambungrejo Bridge originally used WF 700.300.15.28 steel girders and C 300.100.10.16.8 diaphragms,that are susceptible to corrosion, especially during floods. The redesign involves replacing the steel girder with a Prestressed Concrete I Girder (PCI Girder) H-900mm, 170mm thick, produced by WIKA Beton, known for its superior corrosion resistance and construction efficiency. The research methodology includes structural analysis using Robot Structural Analysis Professional (RSAP) software, calculation of prestressing forces, and the design of the prestressing cable layout. The results of this study demonstrate that the use of PCI Girder does not reduce the structural dimensions of the bridge but also proves to be more compatible with the flood water conditions at the site. The total cost required for implementing the new bridge superstructure design is Rp. 4.372.201.